Pedagogical Approaches of a Targeted Social and Emotional Skilling Program to Re-Engage Young Adolescents in Schooling - Katherine Main; Susan Whatman (MDPI AG, 2023)
This paper forms part of a larger study that examined the effectiveness of a targeted social and emotional program to re-engage early adolescents who were already showing signs of disengaging from schooling. Using qualitative methodology, data for this paper come from an in-depth interview with the teacher/facilitator of the program presented as six individual vignette case studies. Each vignette highlights the individual challenges and outcomes of a student who had completed the TLC program. These student cases represented the types of disengaging behaviours students who entered the program were displaying. Findings indicate this short-term targeted social and emotional program is highly successful in re-engaging these students with sustained benefits. The authors call for more awareness of and education for teachers to have the skills to embed targeted social skills when planning their curriculum. This is particularly salient during early adolescence when students begin to exhibit early signs of disengagement.